2018
DOI: 10.1002/ecs2.2136
|View full text |Cite
|
Sign up to set email alerts
|

A model for first‐estimates of species‐specific, age‐specific mortality from centralized band‐recovery databases

Abstract: Citation: Baylis, S. M., P. Sunnucks, and R. Clarke. 2018. A model for first-estimates of species-specific, age-specific mortality from centralized band-recovery databases. Ecosphere 9(4):e02136. 10.1002/ecs2.2136Abstract. Population mortality curves, otherwise known as lifetime distribution functions, can be indispensable in many areas of ecology and environmental management including population viability and stock management analyses, disaster-recovery monitoring, and fundamental evolutionary biology. Yet av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The oldest individual, at 21 years old, represents a little over half of the maximum reported lifespan for this species of 39 years. However, research on age‐dependent survival on Fisher Island birds shows few animals living beyond 25 years post‐first breeding, which would place our oldest individual at closer to 70% of the expected lifespan of approximately 30 years (Baylis, Sunnucks, & Clarke, ; Bradley et al, ). The relationship we have observed with age should be investigated further for older individuals; however, previous studies in mammals have primarily shown linear correlations with age (Maegawa et al, ; Polanowski et al, ; Spiers et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The oldest individual, at 21 years old, represents a little over half of the maximum reported lifespan for this species of 39 years. However, research on age‐dependent survival on Fisher Island birds shows few animals living beyond 25 years post‐first breeding, which would place our oldest individual at closer to 70% of the expected lifespan of approximately 30 years (Baylis, Sunnucks, & Clarke, ; Bradley et al, ). The relationship we have observed with age should be investigated further for older individuals; however, previous studies in mammals have primarily shown linear correlations with age (Maegawa et al, ; Polanowski et al, ; Spiers et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we collected these data because the national‐scale ABBBS mark–recapture dataset has been made open‐access, and estimates of band wear across a wide phylogenetic range are useful in analyses of national‐scale mark–recapture (Baylis et al. ). We hope that our set of estimates will be useful to researchers performing further analyses of the ABBBS dataset and other open‐access mark–recapture datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some population‐structure estimates perform a correction for expected band loss inferred from observed band wear (e.g., Ludwig , Baylis et al. ). The lack of wear‐rate estimates for many taxa limits the ability of researchers to make inferences about population structure for these taxa.…”
Section: Species For Which Wear Rates Of Bands Have Been Reported In mentioning
confidence: 99%
See 2 more Smart Citations